INVESTIGATION OF THE CASTING MOLD FILLING PROCESSES AT USING OF NONSTICK COVERINGS WITH ADDITIVES OF NANO STRUCTURED MATERIAL - D. M. Kukuj; Ju. A. Nikolajchik (Литьë и металлургия)
It is determined that application of nonstick coverings with additives of nanostructured materials in technological process of castings production will enable increase of the casting mold filling degree, reduction of under filling and seals waste.